FACTORS AFFECTING ANXIETY OF MOTHERS WITH LOW-BIRTH-WEIGHT BABIES IN SOUTHWEST SUMBA DISTRICT, EAST NUSA TENGGARA PROVINCE - Conchita Emiliana Ndapa (Journal of Psychiatry Psychology and Behavioral Research, 2021)
The World Health Organization (WHO) states that 60-80% of the infant mortality rate (IMR) occurs due to low birth weight. Low Birth Weight (LBW) contributes 60% -80% of neonatal mortality. The Indonesian Health Demographic Survey (IDHS) in 2017 showed that the incidence of LBW in Indonesia reached 6.2% with a fairly high prevalence. These various effects of LBW are what then causes babies to often require intensive care in the hospital. This condition can then lead to anxiety in parents. Therefore, this study was conducted to determine the factors that influence anxiety in mothers who have babies with LBW conditions in Southwest Sumba Regency. This research was conducted on 20-26 March 2021 with a qualitative approach through interviews and measuring anxiety levels using the HARS questionnaire. The study population was all mothers who had LBW babies in Southwest Sumba. The research subjects were 6 respondents who were selected through the purposive sampling technique. The results showed that there were several factors that influenced the anxiety of mothers with LBW babies, including the mother's age at pregnancy, the amount of parity, and education.Keyword: LBW, Risk Factor, Anxiety